Metabolic engineering for the production of shikimic acid in an evolved Escherichia coli strain lacking the phosphoenolpyruvate: carbohydrate phosphotransferase system - Escalante, Adelfo (BioMed Central, 2010)
BACKGROUND: Shikimic acid (SA) is utilized in the synthesis of oseltamivir-phosphate, an anti-influenza drug. In this work, metabolic engineering approaches were employed to produce SA in Escherichia coli strains derived from an evolved strain (PB12) lacking the phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS(-)) but with capacity to grow on glucose. Derivatives of PB12 strain were constructed to determine the effects of inactivating aroK, aroL, pykF or pykA and the expression of plasmid-coded genes aroG(fbr), tktA, aroB and aroE, on SA synthesis. RESULTS: Batch cultures were performed to evaluate the effects of genetic modifications on growth, glucose consumption, and aromatic intermediate production. All derivatives showed a two-phase growth behavior with initial high specific growth rate (μ) and specific glucose consumption rate (qs), but low level production of aromatic intermediates. During the second growth phase the μ decreased, whereas aromatic intermediate production reached its maximum. The double aroK(- )aroL(- )mutant expressing plasmid-coded genes (strain PB12.SA22) accumulated SA up to 7 g/L with a yield of SA on glucose of 0.29 mol/mol and a total aromatic compound yield (TACY) of 0.38 mol/mol. Single inactivation of pykF or pykA was performed in PB12.SA22 strain. Inactivation of pykF caused a decrease in μ, qs, SA production, and yield; whereas TACY increased by 33% (0.5 mol/mol). CONCLUSIONS: The effect of increased availability of carbon metabolites, their channeling into the synthesis of aromatic intermediates, and disruption of the SA pathway on SA production was studied. Inactivation of both aroK and aroL, and transformation with plasmid-coded genes resulted in the accumulation of SA up to 7 g/L with a yield on glucose of 0.29 mol/mol PB12.SA22, which represents the highest reported yield. The pykF and pykA genes were inactivated in strain PB12.SA22 to increase the production of aromatic compounds in the PTS(- )background. Results indicate differential roles of Pyk isoenzymes on growth and aromatic compound production. This study demonstrated for the first time the simultaneous inactivation of PTS and pykF as part of a strategy to improve SA production and its aromatic precursors in E. coli, with a resulting high yield of aromatic compounds on glucose of 0.5 mol/mol.